ANALYSIS OF STRUCTURAL AND QUANTITATIVE CHANGES IN THE DEVELOPMENT OF LIVESTOCK (Marketing Journal, 2025)
The article provides a statistical analysis of the structural and quantitative changes in the development of cattle breeding in the Republic of Uzbekistan, proposals and recommendations of scientists, ongoing reforms, and trends in the development of lives tock breeding. Recommendations on the use of modern technologies in the network and promising strategic directions are presented.
Keywords: cattle breeding; product; analysis; development; factors; efficiency; indicators; production